Audiodescrição nas TVs abertas de João Pessoa: um estudo das TICs no processo de implantação de recursos de acessibilidade - Ramos, Victor Hugo (2017)
This article reflects the current need to include people with visual impairment in the digital society, specifically through TV and proposes to investigate the lack of information about negligence in the implantation of technological resources of audio description on televisions opened in. The purpose of this study is to provide technologically useful information on audio description systems. Two research methods, the semi-structured interview and the questionnaire, were used with three TV stations and one outsourced TV provider. Among the obstacles to the implementation of the audiodescription resource were the high cost of acquisition of the technologies and the lack of skilled labor to work in the production of such resource.